Feeding profitability is associated with Glossy Black-cockatoo (Calyptorhynchus lathami ssp. lathami) feed tree selection. (1st October 2020) - North, Heather M.; Lamont, Robert W.; Ogbourne, Steven M.; Conroy, Gabriel C.
ABSTRACT: Habitat modification and destruction are known to be responsible for declines in avian taxa. Specialist species such as the vulnerable Glossy Black-cockatoo ( Calyptorhynchus lathami ssp. lathami ) are particularly at risk due to the limited number of Casuarina and Allocasuarina species on which they feed, which is compounded by their propensity for selecting only specific individual feed trees within patches. This study aims to address the lack of understanding surrounding Glossy Black-cockatoo feeding ecology in southeast Queensland, Australia, by examining determinants of tree selection for Allocasuarina littoralis and A. torulosa . We conducted surveys to identify feed and non-feed trees of both Allocasuarina species, and differences between the physical and chemical characteristics of trees, cones, and seeds were investigated. We found that larger trees were preferentially foraged, with nutritional profitability as the primary factor governing tree selection. Feed tree cones had higher seed number and seed mass, with seeds containing higher levels of fatty acids and nutrients than non-feed tree cones. We conclude that further research should aim to delineate the factors contributing to these differences, alongside determining appropriate management strategies to support viable feeding habitat, which is most likely comprised of mixed age patches, capable of maintaining mature trees offering sufficient nutrient reward.